2022
DOI: 10.1186/s13045-022-01364-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint of B7-H3 in cancer: from immunology to clinical immunotherapy

Abstract: Immunotherapy for cancer is a rapidly developing treatment that modifies the immune system and enhances the antitumor immune response. B7-H3 (CD276), a member of the B7 family that plays an immunoregulatory role in the T cell response, has been highlighted as a novel potential target for cancer immunotherapy. B7-H3 has been shown to play an inhibitory role in T cell activation and proliferation, participate in tumor immune evasion and influence both the immune response and tumor behavior through different sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 217 publications
0
33
0
Order By: Relevance
“…CD68 was also found to be a specific marker for macrophages in the inflammatory response and played a crucial role in suppressing T-cell-mediated immunity [ 44 ] ( Figure 1 , Table S1 ). Significant upregulation was observed for the mRNA expression of B7-H3 (CD276), a member of the B7 family that plays an immunoregulatory role in the T-cell response, highlighting this molecule as a novel potential target for cancer immunotherapy [ 45 , 46 ]. Statistical contrast of normal tissue and primary tumor for CD276 mRNA expression in our study showed a significant ( p < 0.0001) 4.03-fold increase in mRNA expression relative to normal tissue ( Figure 1 , Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD68 was also found to be a specific marker for macrophages in the inflammatory response and played a crucial role in suppressing T-cell-mediated immunity [ 44 ] ( Figure 1 , Table S1 ). Significant upregulation was observed for the mRNA expression of B7-H3 (CD276), a member of the B7 family that plays an immunoregulatory role in the T-cell response, highlighting this molecule as a novel potential target for cancer immunotherapy [ 45 , 46 ]. Statistical contrast of normal tissue and primary tumor for CD276 mRNA expression in our study showed a significant ( p < 0.0001) 4.03-fold increase in mRNA expression relative to normal tissue ( Figure 1 , Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, FN1 encodes fibronectin which is involved in cell adhesion and migration processes including embryogenesis, wound healing, blood coagulation, host defense, and metastasis 28 . The identified FN1 AS target encodes the alternatively spliced extra domain B of FN1 (EDB) 29 which is highly expressed in all solid and brain tumor types except RB, with the highest prevalence in OS, EWS, RMS, WT, MEL, HGG and EPN (Extended Data 36,37 .…”
Section: Landscape Of Cse Immunotherapeutic Targets In Pediatric Cancersmentioning
confidence: 99%
“…The B7-H3 gene is located on chromosome 15 (15q24.1) and can be expressed as a type I transmembrane glycoprotein. Cancer overexpression of B7-H3 has been associated with worse prognosis and higher recurrence rates [36,[38][39][40]. Three potential B7-H3 counter-receptors have been identified: triggering receptor expressed on myeloid cells (TREM) like transcript 2 (TLT-2), interleukin 20 receptor subunit α (IL20RA), and phospholipase A2 receptor 1 (PLA2R1) [36,41].…”
Section: B7h3mentioning
confidence: 99%
“…CAR T cells targeting GD2 were safely administered to HRNBL patients without significant toxicity or neuropathic pain. First-generation GD2-CAR T cells showed some anti-tumor effect but were limited by expansion, Multiple newer generations are currently being investigated with varying results [38][39][40]. A recent promising trial of GD2-CAR T cells expressing the inducible caspase 9 suicide gene (GD2-CART01) showed an overall response rate of 63% in heavily pretreated patients with HRNBL [40].…”
Section: Chimeric Antigen Receptor T Cells (Car T Cells)mentioning
confidence: 99%